Neoadjuvant plus adjuvant combined or sequenced vemurafenib, cobimetinib and atezolizumab in patients with high-risk, resectable BRAF-mutated and wild-type melanoma: NEO-TIM, a phase II randomized non-comparative study - Ascierto, Paolo A.; Cioli, Eleonora; Chiarion-Sileni, Vanna; Quaglino, Pietro; Spagnolo, Francesco; Guidoboni, Massimo; Del Vecchio, Michele; Peris, Ketty; Queirolo, Paola; Fioretto, Luisa; Caracò, Corrado; Paone, Miriam; et al. (Frontiers in Oncology, 2023)
Background: Following the increased survival of patients with metastatic melanoma thanks to immunotherapy and targeted therapy, neoadjuvant approaches are being investigated to address the unmet needs of unresponsive and intolerant patients. We aim to investigate the efficacy of neoadjuvant plus adjuvant combined or sequenced vemurafenib, cobimetinib and atezolizumab in patients with high-risk, resectable BRAF-mutated and wild-type melanoma. Methods: The study is a phase II, open-label, randomized non-comparative trial in patients with stage IIIB/C/D surgically resectable, BRAF-mutated and wild-type melanoma, with three possible treatments: (1) vemurafenib 960 mg twice daily from day 1 to 42; (2) vemurafenib 720 mg twice daily from day 1 to 42; (3) cobimetinib 60 mg once daily from day 1 to 21 and from day 29 to 42; and (4) atezolizumab 840 mg for two cycles (day 22 and day 43). Patients will be randomized to three different arms: A) BRAF-mutated patients will receive over 6 weeks (1) + (3); B) BRAF-mutated patients will receive over 6 weeks (2) + (3) + (4); C) BRAF wild-type patients will receive over 6 weeks (3) + (4). All patients will also receive atezolizumab 1200 mg every 3 weeks for 17 cycles after surgery and after a second screening period (up to 6 weeks). Discussion: Neoadjuvant therapy for regional metastases may improve operability and outcomes and facilitate the identification of biomarkers that can guide further lines of treatment. Patients with clinical stage III melanoma may especially benefit from neoadjuvant treatment, as the outcomes of surgery alone are very poor. It is expected that the combination of neoadjuvant and adjuvant treatment may reduce the incidence of relapse and improve survival. Trial registration: EudraCT number 2018-004841-17.